DOXING TERHADAP PEREMPUAN DI MEDIA SOSIAL: ANALISIS HUKUM BERPERSPEKTIF GENDER - Rahman, Yumnannisa' Raissa; Nurani, Fitria; Nurusafa, Naila Marzuna; Azizah, Noviana Dyah; Hidayah, Berliana Ayu; Waljinah, Sri (Jurnal Ilmiah Advokasi, 2025)
The phenomenon of doxing in Indonesia has been increasing alongside the rapid development of digital technology, with women being the most vulnerable group due to power relations and gender bias. Doxing refers to the dissemination of personal data without consent for harmful purposes, including intimidation, harassment, or revenge. This study aims to analyze legal protection for women victims of doxing on social media from a gender perspective. The research employs a descriptive qualitative approach through document analysis, participatory observation, and interviews with seven victims of online gender-based violence (OGBV) and doxing. The findings reveal that doxing takes various forms, including cyberstalking, the dissemination of personal photos, manipulation of pornographic content, and threats. Victims experience psychological trauma, social stigma, and educational barriers. Legally, protections under the Electronic Information and Transactions Law (UU ITE), the Sexual Violence Crime Law (UU TPKS), and the Personal Data Protection Law (UU PDP) remain suboptimal, as doxing is not explicitly regulated and enforcement remains weak. A gender perspective is essential to ensure that legal protections are more responsive to the needs of women victims. This study recommends gender-based policy reformulation, the strengthening of digital literacy, the establishment of a specialized institution for handling digital violence, and psychosocial support for victims. Keywords: Doxing; Women; Online Gender-Based Violence; Legal Protection; Social Media